The Comparative Analysis of Teknolib Library Information System (Library Management System) with SLiMS (Senayan Library Management System) Based on ISO 9126 - Kholifa Artikatama; Rosihan Ari Yuana; Dwi Maryono (Journal of Informatics and Vocational Education, 2019)
Technology is rapidly develop in various aspects of life, especially in the field of education In the world of education, technological developments are applied to the use of library information systems. Nowadays many developers have offered the system for free, one of them is TeknoLIB and SLiMS. This study aims to measure the quality of a library information system using TeknoLIB (Library Management System) and SLiMS (Senayan Library Management System) based on ISO 9126 standards. This study uses 4 research methods, among others: questionnaires, interviews, observation, and documentation. Data analysis was obtained by grouping data from experiment result and personal observation, direct answer to resource person, giving some statement with informant consent, and giving conclusion related to library information system.It can be used as a reference for developers in building a library information system to be able to create a better system. The results of this study indicate that Information Library System TeknoLIB is more qualified in terms of system look compared to SLiMS based on ISO 9126 standards.